Do not panic! enhancing service recovery of nursing services - Yusr, Maha Mohammed; Adam, Mohamad Zainol Abidin; Azzeni, Dayang Nor Saina; Wan Abaid, Wan Mohd Azwan (CIKD, 2018)
Service recovery has been an important issue due to broader social and economic context that shows greater demand for health, care and support which can be concluded that it is critical to study the health care services. Predicting that factors such as top management leadership, teamwork, empowerment, training and commitment is critical to be understood because all these factors will affect the motivation and attitude of employees toward service recovery. Furthermore, employee is one of the source of sustainable competitive advantage to organisations. Nursing staffs are the ones who have variety of jobs to perform and need to juggle with many jobs at many places in the medical profession. Hence, there is no doubt that failure in their service might occur and service recovery is very crucial to make sure that nurses will perform better in-service recovery. This study, therefore, aims to determine the factors influencing service recovery among public nurses. Nurses from various public hospitals in Seberang Perai Utara, Pulau Pinang were chosen as respondents for this study. A total number of 400 questionnaires were distributed to respondents using simple random sampling method. Only 368 questionnaires were returned and used for analysis. The results of correlation analysis and regression analysis have shown that three independent variables (empowerment, training and commitment) had a significant relationship and influenced service recovery. In conclusion, the findings in this study revealed that nurse’s commitment is the most critical factors in service recovery.